A dual RPA-LFD assay for the simultaneous detection of Salmonella typhimurium and Salmonella enteritidis - Liao, Chuan; Pan, Lele; Tan, Meiying; Zhou, Zihan; Long, Shaoping; Yi, Xueli; Li, Xuebin; Wei, Guijiang; Liang, Lina (Frontiers in Bioengineering and Biotechnology, 2024)
Salmonella was one of the most common bacteria that caused foodborne illness, with Salmonella typhimurium (S. typhimurium) and Salmonella enteritidis (S. enteritidis) infections accounting for more than 75% of human salmonella infections. In this study, we developed a method of dual recombinase polymerase amplification (RPA) combined with a lateral flow dipstick (LFD) for the rapid detection of S. typhimurium and S. enteritidis in clinical specimens (stool). The entire reaction process, including amplification and result reading, could be completed within 65 minutes. The detection limits of S. typhimurium and S. enteritidis in pure culture samples were 5.23×10 1 CFU/mL and 3.59×10 1 CFU/mL, respectively. The detection limits of S. typhimurium and S. enteritidis in artificially contaminated samples were 8.30×10 1 CFU/mL and 2.70×10 2 CFU/mL, respectively. In addition, the method had no cross-reaction with other pathogenic microorganisms. The results in clinical samples were fully consistent with those obtained using Bacterial Analysis Manual, with sensitivity and specificity were 100% (8/8) and 100% (17/17) for S. typhimurium and 100% (4/4) and 100% (21/21) for S. enteritidis, respectively. Therefore, the developed dual RPA-LFD assay could be used as a novel tool for simultaneous and rapid detection of S. typhimurium and S. enteritidis in clinical samples.